The impact of physical activity on depressive and anxiety disorders: A literature review - Woźniak, Karolina; Woźniak, Adam; Stasiak, Michał (Quality in Sport, 2024)
Purpose of Research: Depression and anxiety affect over 500 million people globally and are leading causes of disability. While pharmacotherapy and psychotherapy are effective for many, a significant proportion of patients remain resistant. This study examines the role of physical activity as a complementary or alternative treatment for these conditions, focusing on its effects on neuroplasticity, inflammation, and metabolic health. Research Materials and Methods: A systematic review of clinical and experimental studies was conducted using PubMed with keywords like “physical activity,” “running,” “mental disorder,” and “depression.” Included studies were assessed for methodology, participant demographics, and therapeutic outcomes. Basic Results: Physical activity improves depressive symptoms, neuroplasticity, and metabolic health. Running therapy significantly reduces depressive symptoms and inflammation compared to antidepressants. Preclinical studies show exercise reverses depressive-like behaviors and restores hippocampal function in rodents. Meta-analyses confirm the effectiveness of aerobic and strength exercises as standalone or adjunctive treatments, with variations based on age and gender. Conclusions: Physical activity is a cost-effective intervention with significant benefits for mental health, particularly for treatment-resistant patients or those with metabolic comorbidities. Its integration into treatment guidelines could enhance outcomes, emphasizing the need for tailored exercise protocols in future research.